Contemporary Epistemology of Nationalism:: Faltering Foundationalism Contrasted with Holistic Coherentism - Prokic, Uros (Conatus - Journal of Philosophy, 2023)
This inquiry examines the structure of knowledge of nationalism. While numerous studies on nationalism focus on the nature and defining elements of nations, this research explores nationalism discourse from a purely epistemological viewpoint and asks two overarching questions: what are the constitutive beliefs in these various theories and how are they structured? The first section outlines a contemporary foundationalist argument and analyzes two widely accepted theories of nationalism from this theory of knowledge. The study finds that the linear constraints of a foundationalist approach, resting on the existence of non-inferentially justified beliefs, provide a weak framework for understanding the knowledge structures of nationalism. No single element alone can be deemed to be a sufficient basic belief of nationalism that is self-justified. The second part of this research utilizes contemporary coherence theory to assess the interconnected beliefs embedded in nationalism. Examining several theories of nationalism which arguably adopt coherentism, this particular theory of knowledge is shown to provide a more holistic approach. The study concludes that the very definition of nationalism incorporates interconnected beliefs and ideas about ideology, ethnic basis, shared culture and history, as well as unity and autonomy which imply a befitting epistemological refocus away from foundationalism and towards coherentism.